ANALYSIS OF THE PECULIARITIES OF THE TRANSLATION STUDY - Sheraliyeva, Shaxnoza (Журнал иностранных языков и лингвистики, 2023)
In our article, the theory of language arose from the belief that there is much more to translation theory than previously thought, and vice versa. As Gutknecht (2001) claimed, translation theorists use modern linguistic techniques and concepts less systematically. However, two points should be noted: (1) although translation has existed for many centuries, the study of translation has only emerged as a distinct science in the second half of this century, and (2) although translation has adopted concepts and methods from others disciplines, they are still understood as partial sciences. Applied linguistics (Schaffner, 2004, p.2). On the other hand, the direction of translation studies has shifted from linguistic to cultural studies forms in the last fifteen years. There was also a shift towards studies that included functional linguistics and critical language analysis models that placed the text in a sociocultural context. Recent technological advances, which have changed the working conditions of professional translators and researchers and created new forms of translation, have also created new areas of research, some related to the effects of globalization and others to forms of intersemiotic translation. The activity of translation has a long tradition and has been widely practiced throughout history, but in our rapidly changing world, its role has become paramount.